HUBUNGAN DISABILITAS BERDASARKAN UNIFIED PARKINSON DISEASE RATING SCALE DENGAN DISFUNGSI EREKSI PADA PENYAKIT PARKINSON - Ganda Pariama,* Amin Husni,* Endang Kustiowati* (Neurona Majalah Kedokteran Neuro Sains, 2016)
INTRODUCTION ERECTILE DYSFUNCTION ED IS ONE OF THE NONMOTOR SYMPTOMS AND THE INCIDENCE IN PARKINSONS DISEASEPD PATIENTS IS QUITE HIGH CLINICAL SYMPTOMS OF PD MAY INFLUENCE THE OCCURRENCE OR EXACERBATE OF ERECTILE DYSFUNCTION